THE RESULTS OF THE MUNICIPAL ELECTIONS IN 2005–2015, THE KRASNOYARSK KRAI – SOCIOLOGICAL AND POLITICAL ANALYSIS - Vladimir Il’ich Zlotkovskij; Sergej Aleksandrovich Celebrovskij (Krasnoyarsk Science, 2016)
Article is devoted to the analysis of the municipal elections which took place in Krasnoyarsk Krai in 2005–2015. Relevance of a subject of research is caused by that important role which the local governments created following the results of local elections is played in everyday life of people. The used methods – sociological poll of the population and the analysis of documents. The following conclusions are drawn by results of the conducted researches. First, quality of life in municipalities decreases. Secondly, the regional authorities, since 2010, put process of formation and functioning of activity of local governments that allows to speak about a tendency of their nationalization under complete control. Thirdly, selective activity of the population, because of decrease in opportunities of their influence on formation of local authorities, steadily decreases that creates danger of delegitimization of local governments. Results of researches can be used during the developing and realization of regional policy for local government.